2010
DOI: 10.1093/rheumatology/keq035
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial lung disease has a poor prognosis in rheumatoid arthritis: results from an inception cohort

Abstract: RA-ILD is an important and early feature of RA. It is related to disease activity and has a poor prognosis. Further studies are required to determine whether screening for pulmonary disease would identify these patients at an earlier stage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
197
3
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 295 publications
(248 citation statements)
references
References 36 publications
22
197
3
7
Order By: Relevance
“…Other investigators have observed that age, a rheumatoid arthritis disease activity score [13,15], UIP-pattern on HRCT, DLCO % pred at presentation and sex (female protective) [6,15] were significant predictors of mortality. The current study builds on past work from our group: in a prior study, we examined clinical predictors of outcome in RA-ILD defined by lung biopsy and found that age and the presence of any fibrosis on biopsy (UIP, fibrotic NSIP, or unclassifiable fibrosing ILD) predicted mortality [8].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Other investigators have observed that age, a rheumatoid arthritis disease activity score [13,15], UIP-pattern on HRCT, DLCO % pred at presentation and sex (female protective) [6,15] were significant predictors of mortality. The current study builds on past work from our group: in a prior study, we examined clinical predictors of outcome in RA-ILD defined by lung biopsy and found that age and the presence of any fibrosis on biopsy (UIP, fibrotic NSIP, or unclassifiable fibrosing ILD) predicted mortality [8].…”
Section: Discussionmentioning
confidence: 90%
“…ILD is a common manifestation of rheumatoid arthritis, with a prognosis that is generally, but not universally, poor [13]. With 1% of the US population affected by rheumatoid arthritis, and an estimated 7% of all deaths in rheumatoid arthritis related to ILD, ILD is not a trivial concern for rheumatoid arthritis patients and the practitioners caring for them [3].…”
Section: Discussionmentioning
confidence: 99%
“…The most common CTD associated with associated ILD are scleroderma, polymyositis, dermatomyositis, systemic lupus erythematosus and rheumatoid arthritis. In a study by Koduri et al [67] it was noted that in patients with rheumatoid arthritis associated ILD, Risk of death was almost double in patients with low socio-economic status.…”
Section: Interstitial Lung Diseasementioning
confidence: 99%
“…Eroziv eklem hasar›n›n varl›¤›, yüksek eritrosit sedimantasyon h›z›, yüksek titrede romatoid faktör ya da anti-CCP pozitifli¤i ve romatoid nodül varl›¤› ‹AH geliflmesi için risk oluflturmaktad›r. [38][39][40] [41] Klinik semptomlar ortaya ç›kt›k-tan sonra s›kl›kla hastal›k, kötü yönde ilerleme gösterir. Zamanla olan kötüleflme, klinik bulgular›n türüne ve ‹AH'›n radyolojik/histopatolojik tipine göre de¤ifliklik gösterir.…”
Section: Risk Faktörleriunclassified